DPM Tony Tan Visits SMU (Institutional Knowledge at Singapore Management University, 2000)
Deputy Prime Minister Tony Tan visiting with students in Singapore Management University’s library at the Evans Road building on 8 September 2000. Standing, left to right: Dean Tsui Kai Chong, Chairman Ho Kwon Ping, DPM Tony Tan, Trustee Gan See Khem and Deputy President Tan Teck Meng.